Antidiarrheal activity of aqueous leaf extract of Ceratotheca sesamoides in rats (Bangladesh Journal of Pharmacology, 2012)
The antidiarrheal effects of the aqueous leaf extract of C. sesamoides at 25, 50 and 100 mg/kg body weight was evaluated in female rats using gastrointestinal transit, diarrhea and enteropooling induced by castor oil models. The extract was positive for alkaloids, saponins, flavonoids and phenolics. The 25 mg/kg body weight of the extract significantly (p